ASEAN ten economies: converge or diverge? - Habibullah, Muzafar Shah; Din, Badariah; Chong, Choy Yoke (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2017)
The government of the ten ASEAN economies recognized that the disparity in income level among the more developed and the less developed ASEAN economies is substantial. Our question is: Over the years is there any tendency that income disparity among ASEAN is narrowing? Thus, the purpose of the present paper is to examine income convergence and/or divergence in ASEAN ten economies by using the nonlinear unit root test due to Kapetanios et al. (KSS, 2003) and extended by Chong et al. (CHLL, 2008) to permit the test of nonlinear long-run convergence and nonlinear catching-up hypotheses. We apply the KSS-CHLL nonlinear unit root for the test of nonlinear convergence between the ASEAN ten countries with respect to the ASEAN average for the period 1970 to 2015. Generally, our results suggest that out of the ten ASEAN countries, only Indonesia, Malaysia, Singapore and Thailand show nonlinear long-run convergence during the 1980s to 2015; and Cambodia, Laos and Vietnam indicate nonlinear catching-up to the ASEAN average during the same period. However, during other periods – 1970s to 2015 and 1990-2015, the ten ASEAN member countries are diverging from the ASEAN average. This implies that the government of the ASEAN-10 economies have to work harder in order to achieve the aspiration of the ASEAN Economic Community in the far future.